ChemInform Abstract: Novel Porous Ag2S/ZnS Composite Nanospheres: Fabrication and Enhanced Visible‐Light Photocatalytic Activities. Issue 4 (January 2016) - Zhang, Xiaodan; Liu, Xiaojing; Zhang, Ling; Li, Deliang; Liu, Shanhu
Abstract: Monodisperse porous ZnS nanospheres are hydrothermally synthesized from aqueous mixtures of Zn(OAc)2, polyvinylpyrrolidone, and thioacetamide (autoclave, 180 °C, 6 h).